Awareness and use of prenatal diagnosis among Greek women: a national survey - Mavrou, Ariadni; Metaxotou, Catherine; Trichopoulos, Dimitris (Prenatal diagnosis, 1998)
The prevention of genetic diseases through prenatal diagnosis depends to a large extent on the awareness and acceptance of available methods by the public. A national survey was conducted among Greek women in order to explore their attitudes towards and their use of prenatal diagnosis in relation to their lifestyle. The survey was originally addressed to 3000 Greek women 18–65 years of age. Using as a criterion having a child 5 years old or younger, 350 women were eligible for the study. It was noted that 52 per cent of the respondents were adequately informed, while 48 per cent had either superficial knowledge of the subject or no knowledge at all. Amniocentesis was the method that most women were familiar with. The majority said that they were informed by their doctors and the media, and 13 per cent of the participants had prenatal diagnosis during a previous pregnancy. Twenty‐two per cent of those who were not tested were over 35 years of age at the time of pregnancy. There was a significant positive correlation between awareness and acceptance of prenatal diagnosis, on the one hand, and the social, educational and financial profile of the women, on the other. Women aware of prenatal diagnosis adhered more closely to a healthy lifestyle and lived a family‐centred life. © 1998 John Wiley & Sons, Ltd.